2002
DOI: 10.1038/nrg775
|View full text |Cite
|
Sign up to set email alerts
|

Listening to silence and understanding nonsense: exonic mutations that affect splicing

Abstract: Point mutations in the coding regions of genes are commonly assumed to exert their effects by altering single amino acids in the encoded proteins. However, there is increasing evidence that many human disease genes harbour exonic mutations that affect pre-mRNA splicing. Nonsense, missense and even translationally silent mutations can inactivate genes by inducing the splicing machinery to skip the mutant exons. Similarly, coding-region single-nucleotide polymorphisms might cause phenotypic variability by influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,687
5
30

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,940 publications
(1,787 citation statements)
references
References 136 publications
32
1,687
5
30
Order By: Relevance
“…It is possible that changes happening early on in life may set the scene for future longevity, which is an interesting concept given that several genes such as Foxo1, known to be associated with extended lifespan, are developmental genes (Lunetta et al ., 2007). It is very difficult to predict what the consequence of these changes will be to the overall level or pattern of splicing in long‐lived mice or humans, since splice site choice at any given exon: intron junction is determined by the balance of activators and repressors, and that this balance is individually determined for each splice site in each gene (Cartegni et al ., 2002). However, diminished splicing factor expression may be beneficial in younger animals, since both SRSF and hnRNP splicing factors are known to have oncogenic features (Gautrey et al ., 2015; Goncalves & Jordan, 2015; Guo et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that changes happening early on in life may set the scene for future longevity, which is an interesting concept given that several genes such as Foxo1, known to be associated with extended lifespan, are developmental genes (Lunetta et al ., 2007). It is very difficult to predict what the consequence of these changes will be to the overall level or pattern of splicing in long‐lived mice or humans, since splice site choice at any given exon: intron junction is determined by the balance of activators and repressors, and that this balance is individually determined for each splice site in each gene (Cartegni et al ., 2002). However, diminished splicing factor expression may be beneficial in younger animals, since both SRSF and hnRNP splicing factors are known to have oncogenic features (Gautrey et al ., 2015; Goncalves & Jordan, 2015; Guo et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…21 Genetic variations, which cause aberrant splicing, may represent up to 50% of all the deleterious mutations. 30 Depending on tissue localization and/or stage of development, pre-mRNA transcripts may be differentially spliced. We showed that the BRCA2 c.7802A4G variant detected in this study produced 50% of transcripts harbouring a premature stop codon (r.7802_7805delauag) and 50% of transcripts with a p.Tyr2601Cys mutation.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The silent codon214AC C/T polymorphism in exon 7 by itself might lead to the observed phenotypic variability by influencing exonic splicing accuracy or efficiency. The phenomenon of exonic splicing skipping is known from other diseases, such as the neuromuscular disease, Spinal muscular atrophy, as reviewed in Cartegni et al 39 However, the methods for predicting exonic splicing enhancers are still under development. Our results also need to be confirmed in another cohort, as our sample size is relatively small.…”
Section: Discussionmentioning
confidence: 99%